Spatial Variation of Medium Industries Region in Iraq - Azzouz, Ayad Shather Abd (Al-Adab Journal, 2022)
The study of spatial variance of the medium industries region in Iraq sheds light on the establishments of medium industries and knowledge of their characteristics, distribution and spatial variance among the governorates of Iraq. Its ranks and characteristics in terms of the number of establishments, the number of workers, and the value of each of production and supplies. It was found that the governorates of the Kurdistan Region (Sulaymaniyah, Dohuk, and Erbil) as well as the governorates of Baghdad and Diyala occupy advanced levels often, while the activity of medium industries is absent in the governorates (Al-Qadisiyah, Muthanna, and Maysan), and the governorates (Karbala, Wasit, and Dhi Qar) often occupied low levels. When applying some industrial indicators, the most prominent results appeared in the application of the degree of industrialization criterion, where the highest value was recorded in (Dohuk Governorate) and reached (83.4%), while (Karbala Governorate) recorded the lowest value, which amounted to (23.0%). This is an indicator in favor of the latter, as the lower the degree of industrialization, the higher the volume of production compared to the value of the inputs used in it.